MAKLUMAT INDUSTRI DAN SAINS INFORMATION SERVICE FOR COMMERCE & INDUSTRY - Perpustakaan, Hamzah Sendut (Perpustakaan Universiti Sains Malaysia, 2003)
ACER MULLS MSC AS REGIONAL SERVICES HUB Taiwan-based Acer Inc is looking into establishing a base to provide value-added information technology (IT) services for the region in the Multimedia Super Corridor (MSC) in two years' time, sources were quoted. The company is closely studying the possibility as MSC's ready infrastructure and Malaysia's pool of knowledge workers fit well into Acer's plan to diversify into such services.